PENGEMBANGAN MEDIA MOBILE LEARING MATA PELAJARAN BAHASA ARAB METODE DIRECT DI MADRASAH TSANAWIYAH - Muhamad Irwan Wahyudi; Khaerudin Khaerudin (Jurnal Visipena, 2023)
The background in this research based on low utilization of media in Arabic subjects at MTsN 24 Cakung, East Jakarta. This study aims to produce mobile learning media of Arabic with direct methods in Madrasah Tsanawiyah. This type of research is the development research by Hannafin and Peck model using 3 stages: (1) the needs analysis phase, (2) the design phase and (3) the development and implementation phase. The results showed that: (1) The results of the expert review of the subject experts at "very good" criteria (4.00); (2) The results of the expert review of media experts expert judgment at "very good" criteria (3.67); (3) The results of the expert review of instructional design experts at "very good" criteria (3.64); (4) The results of the one to one test for students are in the "very good" criteria (3.43); (5) The results of the small group test for students at "very good" criteria (3.33); (6) The results of the effectiveness test show that the mobile learning media has high effectiveness in improving student’s learning achievement with > = 9.761 > 2.045. Abstrak Penelitian ini dilatar belakangi oleh kurangnya pemanfaatan media pada mata pelajaran Bahasa Arab di MTsN 24 Cakung Jakarta Timur. Penelitian ini bertujuan untuk menghasilkan media mobile learning mata pelajaran Bahasa Arab metode direct di Madrasah Tsanawiyah. Jenis penelitian ini adalah penelitian pengembangan model Hannafin and Peck dengan menggunakan 3 tahapan: (1) Fase analisis kebutuhan, (2) fase desain dan (3) fase pengembangan dan implementasi. Hasil penelitian menunjukkan bahwa: (1) Hasil dari kaji ahli oleh ahli materi berada pada kriteria “sangat baik” (4,00); (2) Hasil dari kaji ahli oleh ahli media berada pada kriteria “sangat baik” (3,67); (3) Hasil dari kaji ahli oleh ahli desain instruksional berada pada kriteria “sangat baik” (3,64); (4) Hasil dari uji one to one kepada siswa berada pada kriteria “sangat baik” (3,43); (5) Hasil dari uji small group kepada siswa berada pada kriteria “sangat baik” (3,33); (6) Hasil dari uji keefektifan menunjukkan bahwa media mobile learning menunjukkan efektivitas yang tinggi dalam meningkatkan hasil belajar peserta didik dengan t-hitung > t-tabel = 9,761 > 2,045.